RELASI JEJARING AKTOR MASYARAKAT SUKU BUGIS SOPPENG DALAM TRADISI MENDIRIKAN RUMAH (MAPPATETTONG BOLA) - Asta Juliarman Hatta; Agus S. Ekomadyo (Prodi Arsitektur UNIVERSITAS KEBANGSAAN, 2020)
Every process and stage in phase of constructing of Indonesia’s vernacular architecture is required the role and contribution of individual or several actors so that procession of house construction can be built due to purposes. According to traditions and beliefs of the Bugis community, there are several actors who have different roles and responsibilities during the process of establishing a Buginese-house. This research aims to explore the influence of the actors’ role who are involved in the process of constructing a traditional Bugis house. Correlation and impact of one actor's involvement with other actors will be reviewed based on the perspective of the Actor Network Theory (ANT) by using descriptive qualitative method. The results revealed that there are 4 stages in the process of building Buginese-house namely the process of constructing a house frame (Mattibang Bola), the process of marking the center of the house (possi bola), the ritual of reading thanksgiving prayer (barzanji), and the process of establishing a house frame (Mappatettong Bola). Founded, Sanro Bola and Panre Bola, namely traditional leaders who have a mandate in the tradition of building houses, are actors who act as controlling actors and are very influential in maintaining the stability of a network in the process of building Buginese-house. Learning from the tradition of building a Buginese-house, the existence of traditional leaders is important, because it has a tradition-based on knowledge base, and this has become a mandate in regulating other actors in working.